2015
DOI: 10.1039/c5cp02148k
|View full text |Cite
|
Sign up to set email alerts
|

The nature of NO-bonding in N-oxide group

Abstract: The nature of the NO-bond in the N-oxide group was investigated by means of combined theoretical calculations (including QTAIM and NBO approaches) and statistical analyses of the contents of crystal structure databases. The N-O bond in the N-oxide group should be classified as the NO donating bond with an important contribution of ON back-donation (of the π-electron type, when available). The visualization of the Laplacian of electron density in the region of an oxygen valence sphere suggests the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 75 publications
3
47
0
6
Order By: Relevance
“…Our recent studies have shown that the N-oxide group may act as an effective proton acceptor in hydrogen bonding [17][18][19]. Also, in case of the crystal structures investigated here, the Noxide group contributes to these kinds of interaction.…”
Section: Intramolecular Hydrogen Bondsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our recent studies have shown that the N-oxide group may act as an effective proton acceptor in hydrogen bonding [17][18][19]. Also, in case of the crystal structures investigated here, the Noxide group contributes to these kinds of interaction.…”
Section: Intramolecular Hydrogen Bondsmentioning
confidence: 95%
“…Various N-oxide interactions stabilizing crystal structures have been investigated [17]. On the basis of theoretical chemistry computations, it has been found that the N-oxide group may act as an effective Lewis base in both hydrogen and halogen bonds [18], even more effectively than the oxygen atom of a carbonyl or ether group. For example, the N-oxide group forms very strong hydrogen bonds with isocyanide with an energy close to 16 kcal/mol (DFT-B3LYP/aug-ccpVTZ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pyrimidopteridine N ‐oxides, the d(N−O) bond lengths are relatively short, with a mean value of about 1.26 Å. In comparison with typical N−O single bonds in hydroxylamines (1.45 Å) and N=O double bonds in nitrosoalkanes (1.27 Å), the crystallographic data suggests that this bond should be considered as a strong non‐polar dative N−O bond, stabilized by π‐type N−O back‐donation, rather than a polar covalent bond N + −O − . Thus, we propose that the NCI originates from lone pair–π‐hole rather than anion–π‐hole interactions.…”
Section: Methodsmentioning
confidence: 95%
“…The QTAIM analysis provides several important quantities such as for example the electron density (ρ) or the Laplacian of the electron density (∇ 2 ρ) calculated at specific points of the molecular space, the latter parameter describes local charge concentration and depletion. The QTAIM method is a powerful tool of structural chemistry allowing to characterize and define various types of bonding of both closed-and shared-shell character [90][91][92]. In the present study QTAIM calculations using the AIMAll program [93] were performed in order to obtain insight into the nature of interatomic bonding around the platinum center in the investigated systems.…”
Section: Methodsmentioning
confidence: 99%